PENANDA GENDER DALAM PERSPEKTIF BAHASA ARAB DAN BAHASA INDONESIA (Sebuah Analisis Kontrastif) - Muhammadun, Muzdalifah (AL-MAIYYAH, 2016)
Indonesia language recognizes set of lingual marking certain gender type. Hierarchically set of lingual can have the character of phonologies and morphologies. In the morphological level procedurally, distinguishable become have the character of mono morphemic and poly morphemic. Set of lingual marker gender is having the character of poly morphemic to refer to forms experiencing certain morphology process. Equally, at gender signify which mono morphemic, in substantial, of course has loaded certain gender component as one of its (the semantic component). On the contrary, at gender signify of poly morphemic, gender character emerges or owned caused by certain morphology process. In Arab language as religion language hardly emphasizes existence of dualism of feminine -masculine. On the other word all noun, if non-masculine surely feminine. There is no space in Arab language for neutral noun. In Arabic structure, masculinity is fundamental which is subject while femininely is branching which is not has ability as subject. Arab Language often treats form of plural as plural masculine, although formally referred by it is a group of feminine, on condition that at least there are one joys in the group. Difference between both hardly explains, where elementary principle in Arab language system tied at principle concord and order word.